2020
DOI: 10.1177/2050312120915399
|View full text |Cite
|
Sign up to set email alerts
|

Authorship growth in contemporary medical literature

Abstract: Objectives: The aims of this study were to investigate authorship trends among publications in high-impact, peer-reviewed specialty journals published within the last decade and to assess how publication practices differ among medical specialties. Methods: The National Institutes of Health’s Portfolio Analysis platform, iCite, was queried for PubMed-indexed case reports, review articles, and original research articles published between 2005 and 2017 in 69 high-impact, clinical journals encompassing 23 medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Considering that 86% of these retractions were in the medical literature, including specialties, we can point out that even in normal circumstances (i.e., not in a pandemic situation), a growth in the number of authors per article can be observed in this field. This is explained by the complexity of multi-disciplinary and multiinstitutional collaboration (An et al 2020). In 4% (n= 2) of the cases, it was not possible to have access to the documents.…”
Section: Erroneous Datamentioning
confidence: 99%
“…Considering that 86% of these retractions were in the medical literature, including specialties, we can point out that even in normal circumstances (i.e., not in a pandemic situation), a growth in the number of authors per article can be observed in this field. This is explained by the complexity of multi-disciplinary and multiinstitutional collaboration (An et al 2020). In 4% (n= 2) of the cases, it was not possible to have access to the documents.…”
Section: Erroneous Datamentioning
confidence: 99%
“…
The number of cited authors per publication has increased substantially over time in the field of medicine. 1,2 This trend of "authorship inflation" has been observed in high-impact medical journals 1 and multiple medical subspecialties, 2 but to our knowledge has yet to be assessed in the field of rheumatology. In this analysis, we describe the number of cited authors in rheumatology publications over a 30-year period.A search of PubMed (NLM) MEDLINE-indexed rheumatology publications from January 1, 1990, to January 11, 2020, was designed by an experienced research librarian and conducted to identify rheumatology clinical practice guidelines, randomized controlled trials (RCTs), systematic reviews and metaanalyses (SRMAs), non-SRMA review articles, and case reports (see Supplementary Data for search terms and strategy, available with the online version of this article).
…”
mentioning
confidence: 98%
“…The number of cited authors per publication has increased substantially over time in the field of medicine. 1,2 This trend of "authorship inflation" has been observed in high-impact medical journals 1 and multiple medical subspecialties, 2 but to our knowledge has yet to be assessed in the field of rheumatology. In this analysis, we describe the number of cited authors in rheumatology publications over a 30-year period.…”
mentioning
confidence: 98%
“…Single-author articles are rare today. [ 34 35 36 ] An et al . counted the number of authors for all original research articles and review articles published in European Urology, the Journal of Urology, Urology, and BJU International from January 2006 to December 2016.…”
mentioning
confidence: 99%
“…In fact, another research has shown that much of this increase in the number of authors cannot be explained by the increased complexity of articles or an increase in the number of collaborative and multicenter studies. [ 34 ] To overcome this problem, the International Committee of Medical Journal Editors issued guidelines as to who can be an author. [ 37 ]…”
mentioning
confidence: 99%